Dasar Pertimbangan Hukum Penyidik Kepolisian Menerapkan Diskresi Sebagai Alternatif Penanganan Perkara Pidana Anak - Djamaluddin R Pasaribu (Jurnal Sostekmas: Jurnal Sosial, Teknologi, dan Pengabdian Masyarakat, 2026)
This study aims to determine the legal basis for police investigators' discretionary use as an alternative in handling juvenile criminal cases and the obstacles they face in exercising discretionary use as an alternative in handling juvenile criminal cases. This study uses normative legal research, which focuses on positive legal norms, specifically statutory regulations. This study primarily utilizes secondary data, consisting of primary and secondary legal materials. The results conclude that the legal basis for police investigators' discretionary use as an alternative in handling juvenile criminal cases is based on both legal and non-juridical factors, including the fulfillment of the primary requirements for a juvenile criminal case to be subject to discretion by investigators, the child in conflict with the law still being educated, and the existence of a request and responsibility from the suspect's parents.